Confirmatory Factor Analysis and further validation of the Comprehensive assessment of Acceptance and Commitment Therapy processes (CompACT) - Bayliss, Katrina (2018)
The current research provides further testing and validation of the newly developed Acceptance and Commitment Therapy (ACT) measure: Comprehensive assessment of Acceptance and Commitment Therapy (CompACT- Francis et al., 2016). To further evaluate the psychometric robustness of the CompACT the current research: (1) completed an intercorrelated and bifactor confirmatory factor analysis (CFA) of the previously identified three-factor structure; (2) retested the psychometric properties (reliability and validity indicators) in an independent sample (n=313); (3) tested the CompACT’s stability over a two-week period (test-retest reliability); and (4) tested the ability to distinguish groups based on clinical screening criteria for distress (CompACT clinical cut-offs). Further testing was then carried out to explore and confirm the construct of the CompACT which included: unidimensional analysis and hierarchical analysis.